Pengaruh E-Service Quality dan Kepercayaan terhadap Minat Beli Ulang Konsumen pada Aplikasi Blibli di Kota Bandung - Doni Kuswandi; Tania Adialita (Jurnal Syntax Admiration, 2024)
The purpose of this research is to examine the influence of e-service quality and trust on the repurchase intention of the Blibli application in the city of Bandung. The instruments used in this study have been declared valid and reliable through validity and reliability tests. The instruments were employed as data collection tools from respondents, namely internet users aged 17 and above who have experience shopping on the Blibli application, with a total of 90 individuals as the subjects of this research. The data collection technique used was cross-sectional or a one-shot study. The data analysis technique employed was simple and multiple linear regression using the SPSS version 25 tool. The findings of this research indicate that e-service quality does not influence repurchase intention, trust has a positive and significant impact on repurchase intention, and e-service quality and trust, when considered simultaneously, have a positive and significant effect on repurchase intention. Meanwhile, other concepts for directly influencing repurchase intention could be proposed by future researchers. The results of this study are also beneficial for the management of the evaluated object and the e-commerce industry in formulating relevant strategies for enhancing the quality of these attributes.